SOSIALISASI PENGENALAN MESIN PRODUKSI BERBASIS CNC SISWA SMK BABAT LAMONGAN - Indrawan, Rizal (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Abstract: Currently, the production process using cnc machines has been able to create various kinds of components to support highly advanced technology. Such as in the fields of health, automotive, and transportation both on land, sea and air. Machine production can also be done conventionally or automatically depending on the type of machine used. In order to provide knowledge and increase the ability of SMK students, it is necessary to hold socialization from universities and institutions that have competence in the machining process. The method of implementation is to provide theory or insight into the introduction of production machines to how to work using various kinds of tools and chisels on various materials that are machined using cnc machines. This is very important to do so that it can be used as a provision for participants in facing global challenges and being able to absorb the needs of workers who are experts in machining using cnc machines. Kata kunci: CNC Machining, Machining Process, Technology, Workpiece, Component